FUNCTIONAL AND CONDITIONAL TRAINING OF TEENAGE SCHOOLCHILDREN - Gafurov Abduvokhid Makhmudovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article reflects the information describing the physical fitness of schoolchildren, as well as its most problematic components, the direction of work on improving the functional and conditioning abilities of students based on experimental methodology.